Exploring the agile-adaptive balanced scorecard benefits towards improving the management accounting system: a case study of Iraqi SMEs / Alhamdi Mohammed, Suzana Sulaiman and Norlaila Md Zin - Mohammed, Alhamdi; Sulaiman, Suzana; Md Zin, Norlaila (Research Management Institute (RMI), 2022)
Economic fluctuations have recently affected the nature of accounting systems in companies, especially small medium enterprises (SMEs). Therefore, this study proposes the Agile-Adaptive Balanced Scorecard (AABSC) as an integrated tool to support and improve the Management Accounting System (MAS) in Iraqi SMEs. The main objective of this study is to explore the role of the AABSC in improving the Management Accounting System (MAS) as a response to economic fluctuations. A qualitative semi-structured interview was conducted in one Iraqi SME, with four top managers from different departments. The interviews are conducted online in Arabic (Iraqi accent) and then translated into English by a linguist expert. The data were analysed and structured using content analysis and Atlas.ti 9 software. Such qualitative analysis is divided into two main categories and four sub-levels. The objectives and advantages of using the AABSC to improve the MAS of Iraqi SMEs are also examined. The adoption of AABSC as part of MAS has assisted companies in strengthening the system. Enhanced competencies are required for staff to increase productivity and the ability to improve their decision-making, which directly contributes to improving the business environment by enhancing the relationship with customers and stakeholders.